Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1017/s0007123414000313
|View full text |Cite
|
Sign up to set email alerts
|

Who Responds? Voters, Parties and Issue Attention

Abstract: Do parties listen to their voters? This article addresses this important question by moving beyond position congruence to explore whether parties respond to voters’ issue priorities. It argues that political parties respond to voters in their election manifestos, but that their responsiveness varies across different party types: namely, that large parties are more responsive to voters’ policy priorities, while government parties listen less to voters’ issue demands. The study also posits that niche parties are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
131
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(146 citation statements)
references
References 71 publications
(65 reference statements)
6
131
0
Order By: Relevance
“…While previous research almost exclusively focused on parties' issue attention in election campaigns focusing either on the American two-party system or concentrating on issue emphasis in election manifestos of political parties in Europe (e.g. Damore 2005;Klüver and Spoon 2014;Sides 2007;Sigelman and Buell 2004;Spiliotes and Vavreck 2002;Spoon and Klüver 2014;Wagner and Meyer 2014), we have provided a novel analysis of parties' issue attention throughout the entire electoral cycle. Based on a quantitative text analysis of more than 40,000 press releases published by German political parties from 2000 until 2010, we were able to explore the day-to-day dynamics of issue competition between political parties.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While previous research almost exclusively focused on parties' issue attention in election campaigns focusing either on the American two-party system or concentrating on issue emphasis in election manifestos of political parties in Europe (e.g. Damore 2005;Klüver and Spoon 2014;Sides 2007;Sigelman and Buell 2004;Spiliotes and Vavreck 2002;Spoon and Klüver 2014;Wagner and Meyer 2014), we have provided a novel analysis of parties' issue attention throughout the entire electoral cycle. Based on a quantitative text analysis of more than 40,000 press releases published by German political parties from 2000 until 2010, we were able to explore the day-to-day dynamics of issue competition between political parties.…”
Section: Resultsmentioning
confidence: 99%
“…But at the same time, previous research examining election manifestos has found considerable evidence for an issue ownership effect (e.g. Green-Pedersen and Krogstrup 2008;Klüver and Spoon 2014). Thus, in order to understand the seemingly contradictory evidence one must bear in mind that two different data sources are analysed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, in order to control for the responsiveness of coalition parties to public opinion, we controlled for voter issue attention as previous studies have shown that political parties respond to the issue priorities of voters (Klüver and Spoon, forthcoming;Spoon and Klüver, 2014). As a result, we expect that coalition parties differentiate less on issues that are highly salient among citizens.…”
Section: Measuring Independent Variablesmentioning
confidence: 99%